Development of Sweet Lime (Citrus Limetta Risso) Pomace Integrated Ricebased Extruded Product: Process Optimization - Kirandeep, Kirandeep; Alam, Mohammed Shafiq; Kumar, Nitin; Singh, Baljit (Journal of Agricultural Engineering, 2018)
Sweet lime is rich in nutrients, but has high waste index. In the present study, efforts were delineated on development of third generation rice-based snacks integrated with pulse powder and sweet lime pomace through extrusion. Optimization of the extrusion process was done by response surface methodology for achieving the maximum possible expansion ratio, water absorption index, water solubility index, crude fibre, antioxidant capacity, protein content, overall acceptability; and simultaneously minimum bulk density, hardness and in range colour change. The developed snack had excellent nutritional, physical and sensory attributes and depicted a scintillating prospect for commercial development. The optimum values of process parameters, using RSM were: 70 % rice proportion (along with 15 % pulse powder and 15 % sweet lime pomace powder) with 12 % feed moisture content, 300 rpm screw speed and 137Â°C die temperature. The overall desirability was 0.62 for extruded product when optimized by RSM.